EFEKTIVITAS MODEL GROUP INVESTIGATION BERBANTUAN MEDIA WATAK KALINYAMATAN TERHADAP PEMAHAMAN KONSEP SISWA - Nurlaely Dwi Astuti; Muhammad Noor Ahsin; Siti Masfuah (PGSD Universitas Muria Kudus, 2020)
This study aims to measure the improvement of students' understanding and also to measure students' learning activities after learning through the Group Investigation (GI) assisted by Watak Kalinyamatan media. This type of research is an experimental research design with Pre Experiment Design. The sample in this study was grade IV SDN 1 Damarjati, with the total of 45 students. Sampling was done by using Purposive Random Sampling technique. Data collection techniques used observation, interviews, tests, and documentation. In Analyzing the data used the final data analysis which includes the normality test, description of the concept understanding analysis, description of the students’ activity description, and hypothesis test that includes n-gain test and t-test.The results of the analysis in this study were (1) there was an improvement in students' understanding of the concepts before and after the GI model of the Watak Kalinyamatan media was applied to the students, (2) P-value = 0.039 bigger than 0.025 H0 was accepted, this means that the average post-test score of students' concept understanding through the GI model assisted by the Watak Kalinyamatan media received a score of ≥ 65, (3) In the learning activities of the students’ meeting 2, 3 and 4 P-value = 0.1075, 0.045, and 0.037 ≥ 0.025, H0 is accepte, this means that the students’ activities after being given learning through GI models assisted by the Watak Kalinyamatan media are ≥ 65.